A Study on Prescribing Trends of Supportive Care Drugs Used in Cancer Chemotherapy in a Tertiary Care Teaching Hospital - S, Ramalakshmi; Ramesh, Anita; Sahini, Kondaviti; Sai Babu, Katta; K, Kousalya; P, Saranya (Indian Journal of Pharmacy Practice)
The encumbrance of cancer is rising worldwide. Cancer therapy has threat within it that go beyond cure. The biggest impediments for cancer patients to face are the toxicities associated with chemotherapy. With this background the study was carried out to describe the prescribing pattern of supportive care drugs prescribed along with cancer chemotherapy. This prospective descriptive study was carried out for a period of two months. All histologically or cytologically confirmed cancer patients of age between 18-65 years on chemotherapy were included in the study. The data on age, sex, demographic information, primary tumour location, lab investigations, chemotherapy, premedication and supportive care medications were recorded in specially designed data collection form. The study population comprised of 50 patients with the mean age of 54.02 ±13.85 years. Majority of them were females, of these, 32% of them were diagnosed with breast cancer followed by ovarian cancer in10% of these patients. Majority of the study population were in third cycle of chemotherapy, predominantly with the combination of paclitaxel and cisplatin in 14% of patients. To avert hypersensitivity reactions and Chemotherapy Induced Nausea and vomiting all patients were pre medicated usually before chemotherapy. The frequently observed supportive care drugs were gastrointestinal drugs (100%), corticosteroids (100%), anti allergics (100%) and analgesics (80%). Other drugs include antibiotics (36%), Nutrition supplements, iron supplements and vitamins. Our study findings convey that all patients during the study period received the best supportive care to improve patients comfort and quality of life.
Keywords: Cancer; Chemotherapy; Premedication; Supportive care